Smart Grid Method for the Lubumbashi Distribution Network Based on Provision of Renewable Energy Resources (Journal of Solar Energy Research Updates, 2022)
Abstract: The development of smart grids (SG) in the electrical network is the subject of many studies nowadays. This new technology seems to be as an additional tool and the perfect solution which the D.R. Congo could use to achieve the objectives of the efficient management of electrical energy, electrical network security, and the inclusion of renewable energy sources. The rise of these new networks brings together many economic issues. This study is essentially focused on the incapability of the National Electricity Company (SNEL) which still retains the monopoly of production and distribution of energy to individuals, industries and mining companies. The incorporation of a system of control and management of the two-ways energy flow between the sources of electricity production and users via an intelligent distribution network, considering several specific constraints and performance required, will allow us to highlight the influence of intelligence in a distribution network as complex as that of the city of Lubumbashi. This study reviews the challenges of renewable energies in the environment of the city of Lubumbashi, the modeling of the distribution network, the introduction of intelligence control in the network and simulation using computer tools to see the contribution of these results to the entire electrical system. Finally, the integration of new renewable energy sources associated with its monitoring system is planned to stabilize this network by increasing the efficiency of the system with 25 percent in power quality.